Criminogenic Risk Score Trajectories of Justice-Involved Youth: An Investigation Across Race/Ethnicity - Kitzmiller, Mary K. (Criminal justice and behavior, 2022)
Juvenile risk assessments are standardized rating tools used by court practitioners to measure criminogenic risk in justice-involved youth. To capture individual fluctuation in risk level over time, juvenile risk assessments are often readministered throughout court supervision. The purpose of this study is to clarify the average criminogenic risk score trajectory among justice-involved youth, both in aggregate and by race/ethnicity. Analyses draw upon a sample of 611 justice-involved youths who received two or more risk assessment scores and were under court supervision for at least 1 year. Using multilevel modeling, findings indicate that risk scores decrease over the first 19 months of court supervision before rebounding in increasingly larger increments. Furthermore, risk scores of White youth appear to be most amenable to reduction over time, while scores of Black youth remain stagnant. Results have implications toward understanding the gains and losses in risk score reduction observed in youth under prolonged court supervision.